Analisis Pengaruh Rasio Likuiditas, Leverage Dan Profitabilitas Terhadap Return Saham Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (2011-2013) - Rositasari, Diah, Ahmad Mardalis, S.E., M.B.A (2015)
Financial ratio analysis is a form or manner commonly used in analyzing the financial statements of a company. The purpose of this study was to determine the effect of the ratio of liquidity, leverage and profitability to return stock at a manufacturing company in Indonesia Stock Exchange 2011-2013. This research is quantitative research and data sources comes from statements of financial data of manufacturing companies listed in Indonesia Stock Exchange 2011-2013. The sampling method using purposive sampling technique, while the method of analysis used is multiple linear regression model. Based on the analysis of data in the discussions can be concluded that the only variable CR significant effect on stock returns. While the variable DER and ROE do not have a significant effect on stock returns